Numerical analysis on the start behavior of rough journal bearings during the gear pump meshing cycle. (August 2020) - Zhu, Jiaxing; Li, Huacong; Fu, Jiangfeng; Liu, Xianwei; Wang, Shang
In this paper, the transient lubrication characteristics of hydrodynamic journal bearings during the external gear pump meshing cycle are studied. In the bearings lubrication calculation part, a numerical model is developed to assess the transient lubrication during the initial start-up of an aero gear pump. The model takes into account the effects of surface topography, asperities contact, and pump start-up speed. In the pump simulation part, the flow inside pump and bearing load environment are analyzed by a computational fluid dynamics model. Then a simulation method is presented to solve the problem of pump-bearings system, considering the pump's influence during bearings lubrication calculation. To gain insight, results of a series of simulations with illustrative examples are presented. The variation of the startup lubrication performance under load conditions corresponding to the pump internal flow field is acquired. The results show that bearings operate from mixed-lubrication to hydrodynamic-lubrication state with changed load-supporting effects during the startup. The load-supporting effects and film rupture boundary are directly related to the pump load fluctuation, but the center trace is slightly influenced except on the hydrodynamic-lubrication state.